OPTIMISASI PRODUKSI USAHA MIKRO KECIL MENENGAH (UMKM) SARI RATU BAKERY DENGAN MENGGUNAKAN METODE PROGRAM LINIER FUZZY - Fakhraini Zahra Afifa; Sajaratud Dur; Fibri Rakhmawati (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
For Law No. 20 of 2008 is a Micro, Small and Medium Enterprises intending to increase and increase its business in the chart so that the national economy is rooted in a just economic democracy. Micro, Small and Prohibiting Efforts (UMKM) have contributed a lot to the development of the Indonesian economy. This significant position has urged many countries including Indonesia to then try to develop MSMEs. This research discusses the optimization of Sari Ratu Bakery profits using fuzzy linear programming. With a tolerance of 10% as the ability of Sari Ratu Bakery and without tolerance as a comparison. The calculation results of the Fuzzy Linear Program with a tolerance of 10%, the profit earned by Sari Ratu Bakery is Rp. 1,288,000 while the profit without adding tolerance is Rp. 1,226,667. While the profit without the Fuzzy Linear Program Production Optimization is Rp. 940,000. Therefore optimizing using Fuzzy Linear Programming is more efficient and can be used for optimizing production profits